ШЕЪРИЙ МАТНДА ИНТЕРРОГАТИВ КОНСТРУКЦИЯЛАРНИНГ ҚЎЛЛАНИЛИШИ - Аллаёров, Т.Р. (SCIENCE and SOCIETY, 2019)
The article is devoted to the study of interrogative sentences in the Uzbek language, using of the term «interrogation» in Linguistics and interrogative situations in different speech forms. Using interrogative situations in the dialogue and monologue is one of the important means of the linguistic formation of the literary-artistic text. The author of the article also analyzes the researches of the scholars on this issue and studies the poetic importance of interrogative sentences in the works of Uzbek poets.